About Recurrence of Epidemic Process of Tuberculosis - A. A. Yakovlev; M. S. Kornilov; E. S. Pozdeeva; L. S. Burnasheva; N. A. Polyakova (Эпидемиология и вакцинопрофилактика)
Relevance. The problem of the cyclical nature of the epidemic process (EP) in various infections, including tuberculosis, remains poorly understood. Aim. To study the cyclical nature of the epidemic process of tuberculosis using the example of the territories of the Primorsky Territory and the Republic of Sakha (Yakutia). The accounting and reporting documents of official medical statistics were used. The incidence of tuberculosis in the population of Primorsky Krai was analyzed from 1951 to 2016, the Republic of Sakha (Yakutia) – from 1962 to 2016. For comparison, we used data on the incidence of tuberculosis in the Russian Federation for 1960–2016. Results and discussion. On the basis of data for more than a 60-year period, the dynamics of the development of EP of tuberculosis among the population of the Primorsky Territory and the Republic of Sakha (Yakutia) was studied in comparison with that of the Russian Federation as a whole. Conclusion. It is shown that the dynamics of the incidence in the analyzed territories is characterized by synchronism and two periods of an increased incidence rate are distinguished in it: the 50s – the beginning of the 70s of the last century and from the end of the 80s to the present.